The Relationship Between a Conducive Learning Environment and Students' Learning Concentration: Evidence from Primary Teacher Education Students - Naufal Qadri Syarif; Muhammad Amran; Aman Islami; Abdul Majid (Universitas Negeri Makassar, 2026)
Sustained learning concentration is essential for academic success in higher education, particularly for pre-service teachers who are expected to develop effective learning management skills. Guided by Attention Restoration Theory (ART) and Self-Determination Theory (SDT), this study examined the relationship between a conducive learning environment and the learning concentration of Primary Teacher Education (PGSD) students at Universitas Negeri Makassar (UNM) Parepare Campus V, Indonesia. A quantitative correlational design was employed. Using Slovin's formula with a 10% margin of error, 81 respondents were selected from a population of 400 students through proportionate stratified random sampling to ensure proportional representation across three academic cohorts. Data were collected using a five-point Likert-scale questionnaire that underwent expert judgment for content validity, Pearson product-moment analysis for construct validity, and reliability testing, yielding a Cronbach's Alpha coefficient of 0.739, indicating acceptable internal consistency. Data were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, linearity test, Pearson product-moment correlation, and the coefficient of determination. The findings revealed that both the learning environment (49% high category) and students' learning concentration (44% high category) were generally at good levels. A significant moderate positive relationship was identified between the two variables (r = 0.550, p < 0.001), with the learning environment explaining 30.2% of the variance in learning concentration. These findings support theoretical perspectives emphasizing that supportive physical, social, and psychological learning environments facilitate students' attentional engagement and academic focus. The study contributes to the literature on learning environments in pre-service teacher education and provides practical evidence for higher education administrators to strengthen classroom facilities, foster supportive lecturer-student interactions, and promote psychologically supportive learning environments to enhance students' learning concentration.